2001
DOI: 10.1046/j.1439-0523.2001.00591.x
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of the genomic composition of Solanum nigrum (+) potato backcross derivatives by somatic hybridization: selection of fusion hybrids by DNA measurements and GISH

Abstract: Fusion experiments were performed with a first (BC1‐6738) and a second (BC2‐9017) generation backcross hybrid of 6x Solarium nigrum (+) 2x potato somatic hybrids with potato cultivars. Because no progeny was obtained from the BC2 genotypes, alternative approaches were sought to overcome the sexual crossing barrier. Five potato genotypes, one of which contains the hygromycin resistance gene, were used in the fusion experiments. All vigorous regenerants were used for the estimation of nuclear DNA content using f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
2
10
0
1
Order By: Relevance
“…Bintje). These results fully correspond with conclusions made by Horsman et al (2001): it is possible to use FC to distinguish between regenerants of parental genotypes, self-fusion genotypes and desired fusion hybrids. Somatic hybrids can be further confirmed by the analysis of molecular markers such as isozymes (Ling and Iwamassa 1994;Thieme et al 1997), rDNA restriction endonuclease digestion patterns (Miranda et al 1997), RFLP analysis (Oberwalder et al 2000) and RAPD-PCR Mourão Filho et al 1996;Thieme et al 1997).…”
Section: Discussionsupporting
confidence: 88%
“…Bintje). These results fully correspond with conclusions made by Horsman et al (2001): it is possible to use FC to distinguish between regenerants of parental genotypes, self-fusion genotypes and desired fusion hybrids. Somatic hybrids can be further confirmed by the analysis of molecular markers such as isozymes (Ling and Iwamassa 1994;Thieme et al 1997), rDNA restriction endonuclease digestion patterns (Miranda et al 1997), RFLP analysis (Oberwalder et al 2000) and RAPD-PCR Mourão Filho et al 1996;Thieme et al 1997).…”
Section: Discussionsupporting
confidence: 88%
“…In our experiment, somatic hybrids C-13 (?) S. etuberosum were confirmed on the different criteria, as in earlier reports, such as RAPD (Rokka et al 1994;Thieme et al 1997;Naess et al 2001;Barone et al 2002;Szczerbakowa et al 2003;Greplova et al 2008), SSR (Nouri-Ellouza et al 2006;Gillen and Novy 2007; (Thieme et al 1997;Maciejewska et al 1999;Oberwalder et al 2000;Horsman et al 2001;Szczerbakowa et al 2003;Greplova et al 2008), and phenotypic assessment (Novy and Helgeson 1994a;Thieme et al 2008;Szczerbakowa et al 2003;Greplova et al 2008). Confirmation of somatic hybrids was revealed by species-specific diagnostic bands (RAPD and SSR) from both the parental components.…”
Section: Discussionsupporting
confidence: 61%
“…Borgato et al (2007) found only tetraploids in S. marginatum (2n = 2x = 24). However, wide variability in ploidy level and the morphology of somatic hybrids from any given fusion combination proved more common (Shi et al 2006;Szczerbakowa et al 2003b;Horsman et al 2001;Szczerbakowa et al 2001). The tetraploids produced in this study probably arose from the asymmetric fusion pnt 8166 ?…”
Section: Discussionmentioning
confidence: 99%